The Organic Life According to Traditional Chinese Medicine with Anticancer Approaches - Shahrajabian, Mohamad H.; Cheng, Qi; Sun, Wenli (Current Nutrition & Food Science, 2022)
The aim of this review was to summarize the most important traditional medinical herbs and plants that are being used in different parts of the world with a focus on a green anticancer approach. The most important impacts of medicinal plants on cancer treatments are prevention of cancer occurrence, decreased side effects, ameliorated post-operative complications, reduced post operative recurrence, reduced tumor growth, maintenance therapy, reduced symptoms and prolonged survival. Alkaloid anti-cancer compounds are pyrrolidine, pyridine, tropane, piperidine, pyrrolizidine, quinolizidine, indolizidine, isoquinoline, oxazole, isoxazole, quinazoline, quinoline, indole serine, purine, β-phenylethylamine, colchicine, benzylamine, abornin, pancratistatin and narciclasine. Anticancer phenolic compounds from plants are flavonol, flavones, kaempferol, luteolin, curcumin, apigenin, chalcone, and cafestol. Anticancer terpenoids compounds from medicinal plants are isoprene, alpha-hederin, galanal A, galanal B, carnosol, oleanane and xanthorrhizol. The most important chemical structures of anti-cancer drugs derived from plants are vincristine, vinblastine, vinorelbine, vindesine, vinflunine, paclitaxel, docetaxel, cabazitaxel, larotaxel, milataxel, ortataxel, tesetaxel, camptothecin, irinotecan, topotecan, etoposide, teniposide, harringtonine and homoharringtonine. Cancer is one of the main and primary causes of morbidity and mortality all over the world. It is a broad group of various diseases typified by unregulated cell growth. The role of plants, especially traditional herbs as a source of organic medicines has been prevalent in many societies, especially in Eastern medicinal science for thousands of years. Traditional medicinal herbs and plants which have both antiviral activity and the ability to promote immunity, would have possible inhibition ability in the initiation and promotion of virus-associated cancers. Medicinal plants should always be considered a great source of novel chemical constituents with anti-cancer effects.
Keywords: plants